Seven faculties in search of a mission: A proposed interdisciplinary course on water literacy. Issue 2 (2nd April 2016) - Sherchan, Samendra; Pasha, Fayzul; Weinman, Beth; Nelson, Fred L.; Sharma, Florence C.; Therkelsen, Jes; Drexler, David
ABSTRACT: In this article we will describe the development of an interdisciplinary general education course focusing on water. As part of a faculty cohort charged with teaching and studying this topic, we considered a number of projects, including community outreach, teacher professional development, and collaborative research. We decided on an interdisciplinary course after examining the relevant issues and recognizing numerous sources of water expertise available within our region.